992 Infrared Thermal Imaging in The Diagnosis and Management of Upper Limb Trauma. (12th October 2021) - Motiwala, F; Liu, C; Southern, S; Jivan, S
Abstract: Aim: Trauma can affect perfusion and thereby the temperature of the injured area. Infrared thermal imaging (IRT) has been used as a non-invasive, non-ionising means of diagnosing and monitoring various pathologies. We aim to evaluate the role of IRT in upper limb trauma. Method: A review of all literature from the Cochrane Database, PubMed, Medline and EMBASE was performed. All papers evaluating infrared thermal imaging in trauma of the upper limb were included. Exclusion criteria included animal or cadaveric studies, and studies not measuring outcomes related to thermal imaging. Results: Six papers were included from a total of 149 papers. There were five observational studies (with limited population numbers) and one case report. Four studies (N = 217) identified significantly higher skin temperatures in fractured limbs compared to non-injured side (p ≤ 0.05). Two studies included follow-ups with skin temperature differences between injured and non-injured sides decreasing over time, consistent with fracture healing times (approximately 3-4 weeks for paediatrics and 6 weeks for adults). One study (N = 9) identified that the presence of activity-related chronic pain in the hand was consistent with higher mean skin temperatures, even at baseline (p = 0.00000795). Conclusions: IRT has been successfully used as a means of diagnosis and monitoring fracture healing in the upper limb. It also shows potential for use in detecting fractures that may not be initially evident on x-ray in the acute setting e.g., scaphoid fractures. Further robust and higher quality studies with larger patient populations are required.